2011
DOI: 10.5127/jep.016611
|View full text |Cite
|
Sign up to set email alerts
|

Processing Biases for Emotional Faces in 4- to 12-Year-Old Non-Clinical Children: An Exploratory Study of Developmental Patterns and Relationships with Social Anxiety and Behavioral Inhibition

Abstract: The present study examined (a) processing biases for emotional facial stimuli in a sample of 355 4-to 12-year-old non-clinical children, (b) developmental patterns of such biases, and (c) to what extent biases were related to social anxiety and the temperamental trait of behavioral inhibition in children of various ages. Processing biases were assessed with a dot probe task and a dynamic emotion recognition paradigm (i.e., morph task), whereas children's levels of social anxiety and behavioral inhibition were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 82 publications
4
23
1
Order By: Relevance
“…In line with the neural parallels between anxiety and BI, adolescents with stable childhood BI also display heightened AB (Perez-Edgar et al, 2010a). However, younger children characterized for BI did not display AB in other studies (Broeren et al, 2011; Perez-Edgar et al, 2011; White et al, in press). In summary, although there is relatively consistent evidence in adults suggesting that AB to threat appears to be causally implicated in the onset and maintenance of anxiety symptoms (Pine et al, 2009), inconsistencies in the youth literature require further research.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…In line with the neural parallels between anxiety and BI, adolescents with stable childhood BI also display heightened AB (Perez-Edgar et al, 2010a). However, younger children characterized for BI did not display AB in other studies (Broeren et al, 2011; Perez-Edgar et al, 2011; White et al, in press). In summary, although there is relatively consistent evidence in adults suggesting that AB to threat appears to be causally implicated in the onset and maintenance of anxiety symptoms (Pine et al, 2009), inconsistencies in the youth literature require further research.…”
Section: Introductionmentioning
confidence: 59%
“…The absence of significant relations between BI and behavioral AB to threat is not uncommon in behavioral (Broeren et al, 2011; Perez-Edgar et al, 2011; White et al, in press) and neuroimaging (Hardee et al, 2013) studies adopting the dot-probe paradigm. Several neuroimaging studies with clinically affected youth also found no associations between behavioral AB and anxiety (Britton et al, 2011; Monk et al, 2008; Price et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There may also be normative developmental changes in attention biases or other developmental factors, such as more efficient attentional control, that differentially contribute to attention biases between ages 5 and 7. Although most recent work in developmental samples does not find a direct association between age and attention bias (Broeren et al., ; Roy et al., ; Salum et al., ; Szpunar & Young, ), in a study with children between the ages of 4 and 12, Broeren et al. () did report that young children tended to show more variability in their RTs and bias scores.…”
Section: Discussionmentioning
confidence: 93%
“…This bias away from threat has also been reported in children with fearful temperaments (Morales et al., ). Several studies have failed to find evidence of a threat‐related attention bias in anxious youth (Waters et al., ) or fearful temperaments (Broeren, Muris, Bouwmeester, Field, & Voerman, ; Pérez‐Edgar et al., ) and several studies have documented a significant attention bias to threat in all children, regardless of anxiety status (Waters, Lipp, & Spence, ). Moreover, there are cognitive training studies in adults and children that found no link between change in attention bias and anxiety (e.g., Hallion & Ruscio, ; Shechner et al., ).…”
Section: Attention Bias To Threat and Anxiety In Childrenmentioning
confidence: 99%
“…However, accuracy in emotion recognition may be improved when children with symptoms of social anxiety are presented with child rather than adult faces (Ale et al 2010), and both accuracy and reaction times for identifying emotional expressions have been found to improve with age (Broeren et al 2011). On the other hand, other research suggests that social anxiety may enhance children’s emotion recognition abilities, with one study showing that children who had greater social anxiety symptoms were better at emotion recognition (Ale et al 2010).…”
Section: Emotion Recognitionmentioning
confidence: 99%